Inclusive education in rural schools: challenges and possibilities / Educação inclusiva nas escolas do campo: desafios e possibilidades - Maria Aparecida Vieira de Melo (Universidade Estadual de Alagoas, 2019)
This article aims to expose reflections on inclusive education in schools in the field, it is still one of the subjects in the education of little discussed field, hence the importance of deepening about this topic. The intent of this paper is to discuss the inclusion in the kids camp schools affected by disabilities of any kind. And more specifically dialogue with the authors that has had this concern contributing to that special attention be offered disabled children of the rural community, particularly the Light Site - Canhotinho-PE to identify the current legislation the specifics that deal with the inclusion in spaces educational and finally realize the importance of enforcing the human rights of persons with disabilities occupy the desks of the schools in their rural community. The problem that guides this discussion is: a human rights education promotes inclusive education in schools in the field? Methodologically this work develops from a literature review, the light of authors who defend human rights, the legal framework of inclusive education and the specificity of rural education. Given the above, we can see that the law contributes to the discussion of the right to inclusion in the educational processes, but are not evident especially in schools of the field, so educators are also not prepared to intervene pedagogically people in need of care specializes in the regular school system.